Societal disruptions and child mental health: Evidence from ADHD diagnosis during the Covid-19 pandemic - Seth Freedman; Kelli Marquardt; Dario Salcedo; Kosali Ilayperuma Simon; Coady Wing (Federal Reserve Bank of Chicago, 2023)
We study how the societal disruptions of the COVID-19 pandemic impacted diagnosis of a prevalent childhood mental health condition, Attention Deficit Hyperactivity Disorder (ADHD). Using both nationwide private health insurance claims and a single state's comprehensive electronic health records, we compare children exposed to the pandemic to same aged children prior to the pandemic. We find the pandemic reduced new ADHD diagnoses by 8.6% among boys and 11.0% among girls nationwide through February 2021. We further show that higher levels of in-person schooling in Fall 2020 dampened the decline for girls but had no moderating effect for boys.
Keywords: I10; I18; I20; 330; Child Mental Health; ADHD; Education; Pandemic